2013
DOI: 10.1097/jnn.0b013e31829db970
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Explore Nurses’ Knowledge in Using the Glasgow Coma Scale in an Acute Care Hospital

Abstract: Educational interventions and guidelines in performing GCS assessment are suggested to maintain and improve knowledge in performing the GCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 4 publications
3
35
1
1
Order By: Relevance
“…Previous studies (Mattar et al 2013, Hien & Chae, 2011) also showed that health care workers working in the ICUs have the highest knowledge. ICU nurses are required to perform the GCS hourly for their patients regardless to the type of the case or how much the case is critical.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Previous studies (Mattar et al 2013, Hien & Chae, 2011) also showed that health care workers working in the ICUs have the highest knowledge. ICU nurses are required to perform the GCS hourly for their patients regardless to the type of the case or how much the case is critical.…”
Section: Discussionmentioning
confidence: 91%
“…Higher scores indicated higher levels of knowledge. This instrument was used before by different studies (Mattar et al 2013, Chan & Matter 2013. The authors developed this instrument as the following.…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evaluations of the scale note that timing is inconstant, components are underutilized, and that components are not assessed and reported in any standardized sequence [16,17]. Further, it has been suggested that differences related to teaching and experience may influence the reliability of the scale [18]. Some author's note that alternative instruments with more robust clinimetrics have emerged and should be considered as a replacement in both research and practice [15], while others suggest that a consensus statement outlines a uniform usage and assessment scheme be utilized to improve the use of the scale between studies [17].…”
Section: Assessment Instrumentsmentioning
confidence: 99%